A hybrid, self-adapting drag-lift conversion wind energy harvesting system for railway turnout monitoring on the Tibetan Plateau. (August 2021) - Wang, Hao; Yi, Minyi; Zeng, Xiaohui; Zhang, Tingsheng; Luo, Dabing; Zhang, Zutao
Graphical abstract: Highlights: An adapting drag-lift conversion wind turbine is designed for harvesting wind energy. The proposed system powers high-speed railway turnout monitoring on Tibet Plateau. A maglev generator and supercapacitors are adopted for power generation and storage. The maximum power coefficient is 0.381 and the maximum output power is 2.46 W. Abstract: Increasing numbers of turnouts are being laid, with the rapid development of high-speed railways on the Tibetan Plateau. Ensuring the proper operation of turnouts has received considerable critical attention. In this paper, a hybrid wind energy harvesting system (WEHS) based on self-adapting drag-lift conversion is designed to power high-speed railway turnout monitoring on the Tibetan Plateau. The system contains three parts: a hybrid vertical axis wind turbine (VAWT), a power generation module, and an energy storage module. Equipped with variable pitch blades, the proposed VAWT can be adaptively converted between lift mode and drag mode in upwind areas and downwind areas, respectively. A maglev generator and supercapacitor are adopted as power generation and energy storage modules. Numerical simulation indicates that the maximum power coefficient of the VAWT is 0.381. According to experiments, the maximum output power of the prototype is 2.46 W, and the maximum average power is 1.08 W. The Sichuan-Tibet Railway was adopted as a case study to investigate the feasibility and the annual power generation of the proposed system is 57.651 MWh. Results illustrate that the proposed WEHS is feasible and practical for powering high-speed railway turnout monitoring on the Tibetan Plateau.